Патентоспособные технические решения, направленные на повышение эффективности функционирования мульчеров - Kovaliok N. S., Ivashnev M. V. (Education environment today: development strategies, 2016)
within the framework of research into the processes of continuous cutting of trees and bushes are considered the patented technical solutions aimed at improving the efficiency of the functioning of mulchers.
Keywords: патент; crushing; измельчение; patent; мульчер; crusher